(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims: (1) to determine the effect of communication on the performance of teacher working groups in Cluster 1 Lempuing Jaya District; (2) to determine the influence of leadership on the performance of teacher working groups in Cluster 1 Lempuing Jaya District; (3) to determine the influence of communication and leadership together on the performance of teacher working groups in Cluster 1 Lempuing Jaya District. This research was carried out in the Lempuing Jaya District Teacher Working Group with a total research sample of 71 teachers. Data collection techniques were carried out through observation, documentation studies, and distribution questionnaires. The validity test uses construct validity, while the reliability test uses Cronbach’s Alpha. Linearity Test and Normality Test. The results of this research show that: (1) there is a partially significant influence between communication on the performance of the teacher’s working group; (2) there is a partially significant influence between communication on the performance of the teacher’s working group; (3) there is a significant simultaneous influence between communication and leadership on the performance of the teacher’s working group.